DEVELOPMENT OF INTUITION IN STUDENTS OF CREATIVE SPECIALTIES (Pedagogy of Higher and Secondary Education, 2010)
In the article development of intuition is examined for the students of creative profession. The analysis of modern scientific approaches is given to the study of intuition and its mechanisms. Intercommunication of visual thought and intuition is empiric explored. It is shown that there is a high index of development of intuition at the high indexes of operatsional'nykh components and judicial descriptions of visual thought.
Keywords: intuition; development; creative professions; research